2013
DOI: 10.1186/1471-2148-13-53
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic development of intestinal length and relationships to diet in an Australasian fish family (Terapontidae)

Abstract: BackgroundOne of the most widely accepted ecomorphological relationships in vertebrates is the negative correlation between intestinal length and proportion of animal prey in diet. While many fish groups exhibit this general pattern, other clades demonstrate minimal, and in some cases contrasting, associations between diet and intestinal length. Moreover, this relationship and its evolutionary derivation have received little attention from a phylogenetic perspective. This study documents the phylogenetic devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 78 publications
(134 reference statements)
3
51
0
1
Order By: Relevance
“…Subtle niche variations in otherwise broad ecological roles probably also increase the area of phenotypic morphospace occupied within broadly similar trophic designations. Differences in specific dietary targets and foraging behaviours of several closely related, nominally 'herbivorous' clades included in this study (Kyphosidae-Girellidae and Scortum, Syncomistes, Pingalla) are associated with notable differences in aspects of tooth shape and length and intestinal morphology [15,21,32]. That multiple adaptive peaks occur in functional morphology of such admittedly broadly classified dietary categories is not surprising.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subtle niche variations in otherwise broad ecological roles probably also increase the area of phenotypic morphospace occupied within broadly similar trophic designations. Differences in specific dietary targets and foraging behaviours of several closely related, nominally 'herbivorous' clades included in this study (Kyphosidae-Girellidae and Scortum, Syncomistes, Pingalla) are associated with notable differences in aspects of tooth shape and length and intestinal morphology [15,21,32]. That multiple adaptive peaks occur in functional morphology of such admittedly broadly classified dietary categories is not surprising.…”
Section: Discussionmentioning
confidence: 98%
“…Here, multiple families have evolved across diverse temperate-tropical regions and macrohabitats, including several marine-to-freshwater transitions. Collective lineages exhibit comparable ecological roles (figure 1a) [15,21], with trophic groups including benthic invertivores, herbivores and carnivores that are frequently associated with distinctive morphotypes relating to body shape, intestinal length and oral anatomy [14,21,22]. If convergence has played a significant role in shaping the macroevolutionary history of the Terapontoidei, we predict ecologically similar species with respect to diet (otherwise phylogenetically distant and often geographically isolated) will converge into the same areas of morphological and dietary space.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to detritus, these species ingested algae and other non-insect aquatic invertebrates. The selection of detritus by these species was expected, independent of its availability in the lakes, mainly because of the foraging behavior, morphology of their digestive tracts, physiological traits as well as by phylogeny (Bowen, 1983;Fugi et al, 1996;Lujan et al, 2011;Davis et al, 2013;Correa & Winemiller, 2014), are factors that limit the use of other items.…”
Section: Discussionmentioning
confidence: 99%
“…The terapontids are one of the most speciose and trophically diverse of Australia's freshwater fish families, exhibiting feeding habits that span carnivorous, insectivorous, omnivorous, herbivorous, frugivorous and detritivorous trophic strategies (Davis et al ., ). Recent comparative studies have demonstrated that a single freshwater invasion by marine terapontid ancestors prompted significantly higher rates of lineage, morphological and trophic diversification (particularly adoption of non‐animal prey dominated diets) in freshwater clades compared to marine counterparts, as well as significant dietary‐ecomorphological correlations across the family (Davis et al ., , , ). With a diversity of feeding modes across freshwater and marine species, terapontids also offer scope for assessing potential phenotypic convergence across the marine‐freshwater interface, the primary macrohabitat divergence for aquatic fauna.…”
Section: Introductionmentioning
confidence: 99%